2017
DOI: 10.3855/jidc.7669
|View full text |Cite
|
Sign up to set email alerts
|

Variable-number tandem repeat markers for Mycobacterium intracellulare genotyping: comparison to the 16S rRNA gene sequencing

Abstract: Introduction: Characterizing Mycobacterium intracellulare responsible for nontuberculous mycobacterial (NTM) infections may aid in controlling outbreaks. This study aimed to compare 16S ribosomal ribonucleic acid (rRNA) sequencing and variable-number tandem repeat (VNTR) genotyping of M. intracellulare strains isolated from clinical samples, and to characterize VNTR clusters associated with NTM infections or cavity formation. Methodology: Sputum samples were obtained from 77 HIV-negative patients with pulmonar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 43 publications
1
1
0
Order By: Relevance
“…The study used a combination of MIRU and VNTR loci, and the association of VNTR clusters, which had clinical significance. NTM infection and the presence of cavity were also related to the VNTR type [77]. Additionally, the study confirmed the similarity between VNTR and PFGE profiling of M. intracellulare patient isolates using seven MIRU loci.…”
Section: Application Of Vntr Methods For Clinical and Epidemiological supporting
confidence: 72%
“…The study used a combination of MIRU and VNTR loci, and the association of VNTR clusters, which had clinical significance. NTM infection and the presence of cavity were also related to the VNTR type [77]. Additionally, the study confirmed the similarity between VNTR and PFGE profiling of M. intracellulare patient isolates using seven MIRU loci.…”
Section: Application Of Vntr Methods For Clinical and Epidemiological supporting
confidence: 72%
“…The overall discriminatory power of the 17-locus typing assay was calculated at 0.66. This was somewhat lower than what was reported for VNTR typing schemes in other NTM, including M. abscessus (13–18 loci, HGDI = 0.96–0.98) 29 , 49 , 50 , M. avium (5–8 loci, HGDI from 0.74 to 0.95) 44 , 51 53 or M. intracellulare (15–16 loci, 0.98–0.99) 27 , 45 , 54 , 55 . At the same time, the genetic diversity of the population studied, measured by the number of different VNTR profiles identified per study sample, was found to be rather moderate when compared to other VNTR-typed NTM (GDI = 0.35 vs 0.1–0.84) 25 , 27 , 29 , 44 , 54 56 .…”
Section: Discussionmentioning
confidence: 59%